Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada PT Alfamart Medan - Kepler Sinaga (LPPM Universitas HKBP Nommensen, 2022)
This study aims to determine the Quality of Service and Price on Customer Satisfaction Consumers Alfamart Jl. Plow 1, Medan. The research method is correlational quantitative and the type of research is explanatory research. The population of all consumers with the number of samples using Convenience Sampling is 67 people. Questionnaire data collection techniques and linear regression data analysis. Testing the hypothesis t test (X1) t count 4.092 > t table 1.998, the significance value of X1 0.000 <0.05 means that service quality has a positive and partially significant effect on customer satisfaction. T test (X2) t arithmetic 10.509 > t table 1.998, the significance value of X2 0.000 <0.0 means that the price has a positive and partially significant effect on customer satisfaction. F test (X1, X2) F count 101.911 > F table 3.14 or significance value (X1, X2) = 0.000 <0.05, meaning X1, X2, simultaneously affects customer satisfaction. Alfamart to further develop quality and affordable prices so as to further increase customer satisfaction.